Popular politics and the English Reformation - Shagan, Ethan H., 1971- (Cambridge studies in early modern British history., 2003)
This book is a study of popular responses to the English Reformation. It takes as its subject not the conversion of English subjects to a new religion but rather their political responses to a Reformation perceived as an act of state and hence, like all early modern acts of state, negotiated between government and people.--Publisher description.